Perceived influence of relationship communication on insurance service quality and customer satisfaction - Effiong, Andem Ita (2019)
Extant literature in marketing and communications has long recognized the importance of effective communication as the essential link for sustainable relationship between organizations and their customers. In spite of its importance, many studies have revealed that practices of communication in relationship marketing in some service firms are fraught with problems, which influence the perceptions of customers about the commitment of those organizations to service quality and customer value. This exploratory study was undertaken to analyze how insurance customers perceive their relationships with insurers through received messages. The study also sought to identify the inherent differences in the perception of relational messages received from insurers by the customers based on gender. A simple random sample of 145 insurance customers were drawn for the study from three insurance agencies. Useful responses were received from 120 automobile insurance policyholders, which represented 82.76% of the sample. Four hypotheses were tested with Pearson Correlation, one-way analysis of variance (ANOVA), and multiple regression analysis. The results of the study suggested significant relationship between relational messages, service quality, and customer satisfaction. In terms of differences in the perceptions of male and female respondents, the study indicated significant differences in the perception of personal values and perceived quality through received messages. Similarly, significant differences were recorded in the perception of message credibility by the female participants as compared with those of the males.  The study also revealed the need for insurance companies to fully imbibe relationship communication with their customers, through assessment of the internal and external situations which surround the information needs of individual customers.